Determination of Gradation of Recycled Mixed Coarse Aggregates for Pavement Base or Subbase by Crushing Fractals - Jianjun Li; Yong Pei; Pengcheng Xu; Hui Chang (Advances in Materials Science and Engineering)
A loading crushing test of recycled mixed coarse aggregates in the same particle diameter range is carried out, and the crushed coarse aggregates are screened, manually sorted, and weighed to study the crushing characteristics of recycled mixed coarse aggregates. The results show that the effect of “reinforcing the strong and discarding the weak” exists between two types of recycled mixed coarse aggregates with different strength in the course of crushing. After crushing, the cumulative mass content under each sieve at all levels and the sieve diameter ratio conform to the geometric fractal characteristics, and the fractal dimension is influenced by the material strength, the initial mixing ratio, and the initial void ratio. On this basis, the fractal dimension of recycled mixed coarse aggregates is determined by the crushing test, and the gradation of recycled mixed coarse aggregates for pavement base or subbase is then determined by fractal dimension. Finally, the mixing amount of recycled clay bricks in recycled mixed coarse aggregates for pavement base or subbase is discussed.